Analisis Vegetasi Gulma Pada Perkebunan Gambir (Uncaria gambir (HUNTER) Roxb) Di Kampung Penurunan Nagari Kayu Gadang, Kecamatan Sutera, Kabupaten Pesisir Selatan - - Yastori; - Chairul; - Solfiyeni (Jurnal Biologi Universitas Andalas, 2014)
The research on vegetation analysis of weed in palm oil plantation (Uncaria gambir (Hunter) Roxb) in Penurunan village, Nagari Kayu Gadang, Sutera, Pesisir Selatan has been conducted from February to April 2013 by using 1 x 1 m 20 plots of purposive quadrate method. The result showed that weed composition in gambir plantation consisted of  15 families, 28 genera and 31 spesies while Index diversity of weed was H’ = 2.54. Axonophus compressus has the highest SDR (Summed Dominance Ratio) 23.02% while Eleusine indica has the lowest SDR 0.40% (2 individuals) in gambir plantation.Keywords : Vegetation analysis, weed, gambir, quadrate method, plot